Spatial Yield Variation and Soil N in a Mature Oil Palm Plantation : A Case Study in Sabah - Tee, Bee Heoh (2001)
One of the major challenges in oil palm plantations in recent times is the lack of proper interpretation of yield maps for site-specific management, and the identification and understanding of the causal factors influencing the variability of oil palm yields. The ability to find and comprehend the soil factors influencing yield variabilities of oil palm will enable us to manage them more efficiently. A study was conducted in a mature oil palm plantation at Sri Kunak Estate, Tawau, Sabah, Malaysia with the objectives (i) to quantify and characterize the spatial and temporal yield variations of fresh fruit bunch (ffb) so as to determine the optimum management zones for oil palm plantations and create possible management zones for site-specific inputs (ii) to quantify and characterize the nature of spatial soil NH4+-N variation as influenced by long-term N fertilizer management (iii) to establish the inter-relationship between fib yields and soil NH/-N so as to develop optimum range of soil NH4+ -N for optimum oil palm growth and production. Two clusters of palms were selected; with and without N fertilizer applications for the past 1 0 years. Soil samples were analyzed for Total N, NH/ -N, N03--N, exchangeable K, and pH. Fresh fruit bunch (fib) yields were summarized on an annual basis. Relationship between fib yields and selected soil properties were investigated using regression analysis. Response of fib yields to soil NH/-N was compared using 6 empirical fertilizer response models. Geostatistical analysis was used to characterize the spatial yield variations of fib and soil NH/-N. Semivariance analysis revealed that within the plots, the increase in semivariance reached a peak at a range of about 2 to 3 -palm distance, suggesting that the optimum management zone for oil palm plantations was 37 palms. Application of N could sustain fib yields above 30 tha-1 y{l . Long-term N fertilizer applications reduced the annual fib yield fluctuations to between 35 and 45%.